Polymer nanocomposites part 2: Optimization of zinc oxide/high-density polyethylene nanocomposite for ultraviolet radiation shielding. (November 2015) - Abou-Kandil, Ahmed I; Awad, A; Mwafy, E
Zinc oxide (ZnO) is a very important compound used in several industries. We synthesized ZnO with different particle sizes and it was incorporated in high-density polyethylene (HDPE) matrix. The resulting nanocomposites were characterized using thermal, physical, and morphological techniques. The mechanical properties of the nanocomposites were also assessed. The nanocomposites were studied for their ultraviolet (UV) absorption properties and were shown to have very good spectral as well as mechanical properties which make them a perfect candidate for applications where UV absorption is essential for example food packing, UV shields, and many other applications.